The effect of misoprostol on the removal of endometrial polyps: A pilot clinical trial - Abbas Aflatoonian; Zohreh Pezeshkpour; Yasamin Mehrolhasani; Nasim Tabibnejhad (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Endometrial polyps are one of the most common gynecological disorders with a high frequency among infertile women. Hysteroscopic polypectomy remains the gold standard for the treatment of endometrial polyps. As alternative treatments, few drugs have been evaluated to date. Objective: To investigate the possible effect of misoprostol on the elimination of endometrial polyps. Materials and Methods: In this clinical trial we examined 30 infertile women whose endometrial polyps were confirmed by transvaginal ultrasound with saline injection. All women were administered 400 mg of misoprostol: 200 mg orally and 200 vaginally. 8 hr later, sonography with saline injection was performed again and all women were examined for the presence or absence of endometrial polyps. Finally, the diagnosis was confirmed for all women using hysteroscopy. The main outcome of this study was the elimination of endometrial polyps after misoprostol administration. Results: The average size of the endometrial polyps was 14.33 ± 4.26 mm, with a range of 7-22 mm. After misoprostol administration, in 12 out of the 30 women who had shown endometrial polyps in the initial examination, no polyp was found. At follow-up it was found that the smallest endometrial polyp that had been eliminated was 8 mm and the largest was 22 mm. Conclusion: The findings of our study revealed that misoprostol can remove up to 40% of endometrial polyps. This drug has the potential to be used as a safe and low-cost first-line treatment before performing hysteroscopic polypectomy.